Effects of the canopy created velocity inflection in the wake development in a large wind turbine array. Issue 3 (September 2016) - Agafonova, Oxana; Avramenko, Anna; Chaudhari, Ashvinkumar; Hellsten, Antti
Abstract: Large Eddy Simulations (LES) are carried out using OpenFOAM to investigate the canopy created velocity inflection in the wake development of a large wind turbine array. Simulations are performed for two cases with and without forest separately. Results of the simulations are further compared to clearly show the changes in the wake and turbulence structure due to the forest. Moreover, the actual mechanical shaft power produced by a single turbine in the array is calculated for both cases. Aerodynamic efficiency and power losses due to the forest are discussed as well.